Test and evaluation of aircraft avionics and weapon systems - McShea, Robert E. (Radar, Sonar & Navigation., 2014)
The following topics are dealt with: MIL-STD-1553; digital data bus; data reduction; data analysis; communication flight test; navigation system; part 23/25/27/29 avionics civil certification; electrooptical system; infrared system; radio detection; radar detection; radio ranging; ranging radar; electronic warfare; air-to-air-air-to-ground weapon integration; avionics integration flight test; unmanned aerial vehicle; night vision imaging system; NVIS; helmet mounted display; HMD; test management; and operational test.